2021
DOI: 10.3390/ph14020159
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Type Agnostic Therapy Carrying BRAF Mutation: Case Reports and Review of Literature

Abstract: Background: Precision medicine is based on molecular and genotypic patient characterization to define specific target treatment. BRAF mutation is an oncogenic driver, and the Cancer Genome Atlas has identified BRAF mutations in different cancer types. Tumor type agnostic therapy is based on targeting genomic alterations, regardless of tumor origin. In this context, novel therapeutic agents including BRAF and MEK inhibitors based on the molecular landscape in solid tumors have been investigated. Case presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
1
3
0
2
Order By: Relevance
“…The findings from the ROAR study are also complementary to available case reports supporting the efficacy of dabrafenib plus trametinib in various BRAFV600E mutation-positive tumors, including breast cancer 21 , pancreatic cancer 22,23 , salivary duct cancer 24 , Bellini duct cancer 25 , pituitary tumor 26 , ameloblastoma 27 , histiocytic sarcoma 28 and gynecological malignancies 29,30 . Some of the cancers reported here are ultra-rare cancers and have never been studied before with BRAFV600 inhibitors in clinical trials.…”
Section: Discussionsupporting
confidence: 58%
“…The findings from the ROAR study are also complementary to available case reports supporting the efficacy of dabrafenib plus trametinib in various BRAFV600E mutation-positive tumors, including breast cancer 21 , pancreatic cancer 22,23 , salivary duct cancer 24 , Bellini duct cancer 25 , pituitary tumor 26 , ameloblastoma 27 , histiocytic sarcoma 28 and gynecological malignancies 29,30 . Some of the cancers reported here are ultra-rare cancers and have never been studied before with BRAFV600 inhibitors in clinical trials.…”
Section: Discussionsupporting
confidence: 58%
“…This research reveals that treated ICC patients with combined inhibition of BRAF and MEK showed favorable outcomes and tolerable side effects. Furthermore, there have been 6 cases reporting inhibition of BRAF and MEK combined in treating cholangiocarcinoma (CC) with BRAF V600E mutation (summarized in ▶ Table 1 [28,29,30,31,32]). These 6 patients all achieved obvious tumor remission, progression-free, and one of them survived tumorfree with no signs of recurrence for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a dismal response rate of 12% (one partial response/eight total patients) was reported with vemurafenib, likely related to the high burden of disease and poor patient conditions. Later, successful combination therapies involving BRAF inhibitors (i.e., vemurafenib or dabrafenib) for the treatment of metastatic CCAs were reported [ 52 , 53 ]. In most cancers bearing BRAF mutations, patients treated with BRAF inhibitors develop disease progression within a few months from the start of treatment.…”
Section: Inhibition Of Braf Pv600e In Ccamentioning
confidence: 99%